Eksplorasi Permasalahan Kebutuhan Media Inovatif Sebagai Dasar Pengembangan Game Berbasis Gamifikasi - Dwi Oktaviana; Utin Desy Susiaty (Universitas Islam Jember, 2026)
The objectives of this research are: 1) To describe various problems faced in learning fractions in Junior High School students, both from the perspective of teachers, students, and the learning process in general; 2) To describe the needs and expectations of teachers and students for more innovative, interactive, and fun learning media; 3) To formulate the initial characteristics of game-based learning media with a gamification approach that suits students' needs and is relevant for learning fractions. This research uses a qualitative approach with an exploratory case study type, with analysis according to Miles & Huberman. The results obtained are: 1) Students experience conceptual difficulties in understanding fraction material, procedural difficulties in completing fraction operations, and learning is still conventional and does not facilitate student activity; 2) There is a strong need for innovative technology-based learning media; 3) Gamification-based educational games have great potential to be developed as the main solution. Keywords: problem exploration, innovative media, gamification